(untitled) (Proceedings of the International Conference on Education, 2025)
To achieve the goal of human resource development in line with globalization trends, Vietnam has identified strengthening international integration. Today’s students not only need specialized knowledge but also must possess soft skills such as communication, teamwork, creativity, and problem-solving abilities. On the other hand, modern technology has changed the teaching and learning methods in universities. Therefore, universities need to adjust their curricula to meet these requirements, as well as enhance international cooperation, student exchange, and integrate technology into teaching. Thus, reforming teaching management contributes to improving the quality of education, developing high-quality human resources, and increasing the competitiveness of Vietnamese universities on the international stage. Through teaching management reforms, universities can better prepare students, helping them adapt to the demands of the global labor market and international education standards. The method of theoretical analysis and synthesis is used to study, analyze, and evaluate relevant documents to better understand the nature of the research issue. Based on this, the theoretical system of the topic is formed, and data is analyzed and processed to assess the current situation, limitations, and challenges in the reform of teaching management in Vietnamese universities, such as digital transformation management, curricula and teaching methods, autonomy, improving the quality of lecturers, quality of graduates, infrastructure for teaching, and international cooperation. From there, solutions are proposed to contribute to reforming teaching management, improving training quality, and increasing international integration, helping students and universities in Vietnam to develop strongly and compete internationally